Medical waste including hazardous waste - Agata Anna Salwa (Kazimierz Wielki University, 2018)
Introduction and purpose of the work. Medical waste is a special type of waste generated as a result of conducting exceptional activities (related to, among others, saving human life) or related to a specific place (eg a hospital). They are a by-product of health care, arising at various levels of its activity. "Medical waste" means waste arising in connection with the provision of health services and the conduct of research and scientific experiments in the field of medicine. Summary. The data show that the amount of medical waste generated (especially those hazardous, because they constitute the major part of this group), will increase year by year. It seems almost impossible to remedy this phenomenon in any way. That is why their proper management is so important. Key words: medical waste, hazardous waste, hazard